Review of mangrove foraminifera from the Guaratiba tidal plain, Rio de Janeiro, SE Brazil, collected in the early 70’s - Laut, Lázaro L. M.; Koutsoukos, Eduardo A. M.; Rodrigues, Maria Antonieta C. (Anuário do Instituto de Geociências, 2006)
Abstract